Rozwiązane

Zad 1. ( 4pkt)

Uporządkuj jednomiany.

a) d * c* 2* c =

b) z* y * 0,5 * y * ( - 3)=

c) 4*a*a*b*b * ( - 3) *a =

d) 0,3*x*x*(- 4) * y*Y*y * ( - 1) =

Zad 2.

Zredukuj wyrazy podobne.

a) – 2 - 2a + 3 =

b) 3x – 4y - 2x – 4 – x – 2y + 5 =

2 2

c) 2x + 4x – 5x + 6x – 7=

d) 2ab – 3a + 4ab – 4a + 2b – 1 =



Odpowiedź :

Odpowiedź:

zad. 2

a) -2-2a+3= 1-2a

b) 3x-4y-2x-4-x-2y+5= 1-6y

c) 2x+4x-5x+6x-7= 7x-7

d) 2ab -3a+4ab-4a+2b-1= 6ab-7a+2b-1

zad. 1

( jeżeli ta "* " to mnożenie to : )

a) d * c* 2* c = 2c²d

b) z* y * 0,5 * y * ( - 3)=1,5y²z

c) 4*a*a*b*b * ( - 3) *a =-12a³b²

d) 0,3*x*x*(- 4) * y*Y*y * ( - 1) =1,2x²y³

Inne Pytanie